Peran Media Sosial dalam Membangun Opini Publik terhadap Pemimpin Politik - Arni Damayanti; Eko Purwanto; Maydiyan Pangesti; Putri Dwi Hastuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The rapid growth of social media in the last five years has transformed the landscape of political communication and significantly influenced how public opinion toward political leaders is formed. Platforms such as TikTok, Instagram, and X (Twitter) have become key arenas for shaping political perception through visual narratives, short-form videos, and direct engagement between leaders and citizens. Recent studies highlight that algorithmic curation plays a crucial role in selectively amplifying certain political messages, which consequently affects how users construct their political judgments. Furthermore, users’ trust in the credibility of digital sources and the level of audience engagement have been shown to strongly determine the legitimacy and public support received by political leaders. This literature-based study synthesizes findings from recent international journals to explain how social media functions not only as a space for information dissemination but also as a strategic instrument for opinion formation and image construction in the political sphere.